1977
DOI: 10.1056/nejm197706092962306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surveillance on the Number of Hysterectomies in the Province of Saskatchewan

Abstract: In 1972 the College of Physicians and Surgeons of Saskatchewan appointed a committee to study hysterectomies because the Saskatchewan Department of Health had data showing that the annual number of hysterectomies carried out in the province had increased by 72.1 per cent between 1964 and 1971, whereas the number of women over 15 years of age had increased by 7.6 per cent. The committee compiled a list of indications for hysterectomy. Any hysterectomy carried out for one of these reasons was classified as just… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Dick et al (6) similarly explain the dramatic increase of hysterectomies in the Canadian province of Saskatchewan between 1964 and 1971 as a consequence of the introduction of compulsory health insurance in Canada.…”
Section: Tons Appe Dandcur Hyst Hern Hemo Cholmentioning
confidence: 99%
“…Dick et al (6) similarly explain the dramatic increase of hysterectomies in the Canadian province of Saskatchewan between 1964 and 1971 as a consequence of the introduction of compulsory health insurance in Canada.…”
Section: Tons Appe Dandcur Hyst Hern Hemo Cholmentioning
confidence: 99%
“…In 1972, the College of Physicians and Surgeons of Saskatchewan appointed a study committee in response to the finding that the annual number of hysterectomies in the province had increased at a rate ten times greater than the increase in the number of adult women in the population during the study period. As the result of stipulating approved indications for hysterectomy, the number performed in the province dropped by one-third during a four year period (17). In similar fashion, Winnberg et al (\8) found that the feedback of information to the Vermont State Medical Society on disproportions in the number of tonsillectomies was associated with a significant red uction in state-wide rates.…”
Section: Effects Of Data Feedback On Physician Behaviormentioning
confidence: 92%
“…In a similar study in Saskatchewan, a group of gynaecologists decided under which clinical circumstances a hysterectomy was 'justified' or 'not justified' (Dyck et al 1977). Feedback of 'justified' and 'not justified' operating rates resulted in a 32.8% decrease in the number of hysterectomies performed in the province between 1970 and 1974.…”
Section: Reducing Overtreatmentmentioning
confidence: 99%